A "worm"-containing viscoelastic fluid based on single amine oxide surfactant with an unsaturated C22-tail1. Issue 25 (21st March 2015) - Zhang, Yongmin; An, Pengyun; Liu, Xuefeng
<x xml:space="preserve">Abstract</x> A "worm"-containing viscoelastic fluid based on single unsaturated C22-tailed amine oxide surfactant shows pH-controlled thermo-thickening behaviour.